PENGARUH FOMO DAN SOCIAL MEDIA INFLUENCER TERHADAP KEPUTUSAN INVESTASI DENGAN LITERASI KEUANGAN SEBAGAI MODERASI - Zila Armeyanti; Ayu Umyana; Angga Permadi Karpriana (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study discusses the impact of Fear of Missing Out (FOMO) and the influence of Social Media Influencers on young people's investment decisions, as well as the role of financial literacy as a moderating variable. With the development of technology, young people are more ensily exposed to investment information, which is often influenced by social media. The purpose of this study is to examine the relationship between FOMO, social media influencers, and investment decisions, and how financial literacy moderates the effect. The research method used is quantitative with a causal associative design, involving 236 respondents who are generation and millennials in Indonesia. Data analysis was conducted using SmartPLS 4.0. The results showed that FOMO and social media influencers have a significant positive effect on investment decisions. Financial literacy is proven to moderate the influence of FOMO, but does not moderate the influence of social media influencers. This study emphasizes the importance of financial literacy to improve more informed investment decisions among the younger generation The practical implication is that the younger generation is expected to be more critical in investing and not merely follow trends